Stock Market Developments and Private Consumer Spending in Emerging Markets - Funke, Norbert (International Monetary Fund, 2002)
Using a panel of 16 emerging markets, the paper finds a small but statistically significant effect of stock market developments on private consumption spending. In the short run, a 10 percent decline in the annual real stock market return is associated with a reduction in real private consumption by around 0.1-0.3 percent on average. There is evidence that the link between stock market fluctuations and private consumption has become stronger during the 1990s as stock markets in emerging economies have broadened and deepened. However, there is no significant evidence that the influence is asymmetric. Stock price declines do not have a different impact on consumption than stock price increases